2020
DOI: 10.1016/j.jve.2020.100019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on people living with HIV: A review

Abstract: There is great concern about the impact of COVID-19 among the nearly 40 million people living with HIV (PLWH) worldwide. In this review, we surveyed current literature and found no evidence of higher prevalence of COVID-19 among PLWH but equivocal data on increased mortality and worse clinical outcomes. Having HIV does not confer protection against severe manifestations of COVID-19. Several studies looking at antiretroviral drugs against HIV to treat SARS-CoV-2 have shown no mortality benefit. Thus, there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
3
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 40 publications
7
79
3
9
Order By: Relevance
“…This work builds on previous reviews on specific sexual health issues and COVID-19, which generally focused on the intersection of HIV and COVID-19 and did not examine sexual health more broadly. [6][7][8] We found that MSM may be moving back toward pre-pandemic levels of sexual activity. Abstinence-based strategies to limit HIV transmission are generally ineffective 133 and it is not reasonable to expect people to refrain from sexual activity amid a pandemic.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This work builds on previous reviews on specific sexual health issues and COVID-19, which generally focused on the intersection of HIV and COVID-19 and did not examine sexual health more broadly. [6][7][8] We found that MSM may be moving back toward pre-pandemic levels of sexual activity. Abstinence-based strategies to limit HIV transmission are generally ineffective 133 and it is not reasonable to expect people to refrain from sexual activity amid a pandemic.…”
Section: Discussionmentioning
confidence: 82%
“…While several reviews have sought to synthesise existing and fast-changing evidence on COVID-19 and health outcomes, little attention has been paid to the pandemic's effects on sexual health and wellbeing. There have been, however, several reviews focused on HIV specifically, [6][7][8] but not on sexual health more broadly. Sexual health is a central feature in overall health and well-being, and in the socioeconomic development of communities and countries 9 ; understanding if and how the COVID- 19 11 Reporting of results conformed to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasingly consolidated body of evidence on COVID-19 in the general population, the interaction between SARS-CoV-2 and HIV infection is still unclear and data are, at times, conflicting. 11 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Firstly, outpatients' visits and treatment have been interrupted or postponed because of the lockdown [8] and the fear of contracting COVID-19 has led to decreased engagement with care among PLWH in several countries [23][24][25][26][27]. Additionally to complications related to HIV disease progression, an incorrect management of HIV could lead to an increased risk contracting COVID-19 and experiencing complications.…”
Section: Introductionmentioning
confidence: 99%